Pendampingan Digitalisasi Pencatatan Akuntansi UMKM Warung Sayur melalui Aplikasi BukuWarung - Florasita Dewi Do’a; Hasim As’ari (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2026)
Vegetable stall businesses represent a common form of micro-enterprise that meets consumers' daily needs, including in the Depok District. However, most business owners have yet to adopt proper and adequate financial record-keeping practices, relying instead on manual methods. This makes it difficult to control and evaluate business financial management. This community engagement initiative aimed to provide guidance on digitizing accounting records for vegetable stall MSMEs using the BukuWarung application and to enhance the digital financial literacy of business owners regarding digital financial management. A quantitative descriptive approach was employed, involving observation, interviews, documentation, and direct assistance provided to vegetable stall owners in the Depok District. Observations revealed that business owners gained a better understanding of and improved skills in using the BukuWarung application, becoming capable of independently recording income, expenses, and business receivables and payables. The initiative demonstrated that implementing a guidance program for digitizing accounting records via the BukuWarung application significantly contributed to improving the financial management capabilities of vegetable-trading MSMEs. These findings suggest the potential for applying similar guidance models to MSMEs in other regions to foster broader digital financial literacy.